(untitled) (Journal of Medicine, 2009)
A prospective type of analytical study was carried out on 106 patients with breast pain to analyze the causes of breast pain. This study was conducted from August, 2002 to January 2004 at breast clinic of Bangladesh Medical College Hospital (BMCH) and at Department of Surgery of BMCH. Sampling was done purposively and a structured questionnaire was used for data collection by interviewing followed by examining the patient in the first phase. In the second phase, Mammography and FNAC (Fine Needle Aspiration Cytology) was done. Majority of the patients (35.8%) were in the age group of 21- 30 years and the mean age was 27.61± SD10.5 years. About 48.1% breast pains were due to ANDI (Aberration of Normal Development and Involution) and among the other causes nonspecific pain 15.1%, breast abscess 14.2% and carcinoma of breast were only 1.9%. The performance status of all the patients were in between 0- 1. Mammography was done in 54 patients and of them 44 was found positive for fibrocystic disease (41 cases) and fibroadenoma (3 cases). FNAC was done in 50 patients and 36 were found positive with fibroadenoma (22 cases), fibrocystic change (8 cases), chronic breast abscess (2 cases), mitotic lesion (2 cases), and neurofibroma (2 cases). So painful breast diseases are helpful in seeking further medical care for appropriate intervention Keyword: Breast pain, Mastalgia, ANDI. doi: 10.3329/jom.v10i2.2818 J MEDICINE 2009; 10 : 77-81